Pathologic Response Rates after Neoadjuvant Therapy for Sarcoma: A Single Institution Study - Crystal Seldon (Cancers, 2021)
(1) Background: Pathologic necrosis of soft tissue sarcomas (STS) has been used to determine treatment response, but its relationship to neoadjuvant treatments remains indeterminate. In this retrospective, single institution study, we hypothesized that neoadjuvant chemoradiation (NA-CRT) yields higher rates of pathologic complete response (pCR) than neoadjuvant radiation (NA-XRT) or chemotherapy (NA-CT) alone. (2) Methods: Patients with extremity STS between 2011–2020 who received neoadjuvant treatment were included. pCR was defined as percent necrosis of the surgical specimen greater than or equal to 90%. (3) Results: 79 patients were analyzed. 51.9% of the population were male with a mean age of 58.4 years. 49.4% identified as Non-Hispanic White. Twenty-six (32.9%) patients achieved pCR while 53 (67.1%) did not. NA-CT (OR 15.82, 95% CI = 2.58–96.9, p = 0.003 in univariate (UVA) and OR 24.7, 95% CI = 2.88–211.2, p = 0.003 in multivariate (MVA), respectively) and NA-XRT (OR 5.73, 95% CI = 1.51–21.8, p = 0.010 in UVA and OR 7.95, 95% CI = 1.87–33.7, p = 0.005 in MVA, respectively) was significantly associated with non- pCR when compared to NA-CRT. The analysis also demonstrated that grade 3 tumors, when using grade 2 as reference, also had significantly higher odds of achieving pCR (OR 0.23, 95% CI = 0.06–0.80, p = 0.022 in UVA and OR 0.16, 95% CI = 0.04–0.70, p = 0.015 in MVA, respectively). (4) Conclusion: NA-CRT yields superior pCR compared to other neoadjuvant regimens. This extends to higher grade tumors.